Wideband Dual-Polarized Quasi-Omnidirectional Antenna with High Isolation for Mobile Applications in High-Speed Vehicles - Peng Luo; Chengguo Nie; Qing Gong; Yuehui Cui (International Journal of Antennas and Propagation)
A new wideband dual-polarized (DP) quasi-omnidirectional antenna is proposed. The DP antenna consists of a vertical slot for horizontal polarization (HP) and a folded horizontal slot for vertical polarization (VP). A tapered strip is employed to coupling feed the vertical slot while a straight strip is used to excite the horizontal slot. Due to the coupling feed and the orthogonality between the vertical and horizontal slots, the DP antenna features a wide bandwidth and a very high isolation. The simulated isolation is higher than 70 dB, although the measured isolation is about 50 dB. As experimental results indicate, the DP antenna realizes an impedance bandwidth (BW) of 45% (1.7–2.73 GHz) with quasi-omnidirectional radiation patterns for both HP and VP. The DP quasi-omnidirectional antenna may be packaged into a radome with a shape of a blade for mobile applications in high-speed vehicles.